Posterior and Anterior Fusion for Severe Cervical Kyphosis in a Patient with Chondrodysplasia Punctata: A Case Report. Issue 1 (January 2021) - Kato, Shuzo; Fujita, Nobuyuki; Suzuki, Satoshi; Tsuji, Osahiko; Nagoshi, Narihito; Okada, Eijiro; Yagi, Mitsuru; Watanabe, Kota; Nakamura, Masaya; Matsumoto, Morio
Abstract : Case: A 4-year-old girl with spastic gait and hand clumsiness who was diagnosed with cervical myelopathy caused by atlantoaxial dislocation and midcervical severe kyphosis associated with chondrodysplasia punctata (CDP). The patient underwent posterior instrumentation and anterior spinal fusion and successful correction with osseous fusion was obtained 8 months after surgery. In addition, the preoperative neurological symptoms were completely recovered. Conclusion: Owing to the characteristics of CDP, the treatment for the cervical lesion is extremely complicated. Successful stabilization and improvement of the neurological symptom were achieved by combining posterior and anterior fusion with instrumentation in this case.